Determining the Prevalence and Risk Factors Associated with Leishmaniasis among Residents of Rural Marigat Sub-County, Baringo County- Kenya - Gwandi , Martin Philipo; Odongo, Alfred Owino; Kirira, Peter G.; Jeruto, Esleen (Current Overview on Disease and Health Research Vol. 1, 2022)
Leishmaniasis is a parasitic and vector-borne disease with two primary forms: Cutaneous Leishmaniasis and Visceral Leishmaniasis, respectively, with an annual global incidence of 0.95 and 0.3 million cases. The study looked on the prevalence of Leishmaniasis and the risk factors linked with it in Kenya's Baringo County. The researchers used a mixed method analytical cross-sectional study design. In Kenya's Baringo County, 333 heads of households were recruited for the study. To enroll study participants, researchers utilized purposive and multistage sampling procedures. Leishmaniasis was reported by 96 out of 333 subjects, resulting in a prevalence of 28.8%. Increased odds of contracting Leishmaniasis were associated with living in a temporary house (OR = 5, 95% CI 2.64 – 9.44), Living below the poverty line (OR = 2.4, 95% CI 0.23 – 0.78), primary level of education (OR = 8.6, 95% CI 0.14 – 0.97), presence of termite hills (OR = 7.6, 95% CI 0.60 – 0.97) and presence of soil cracks (OR = 3.6, 95% CI 0.16 – 0.50). Having bed net (OR = 3.5, 95% CI 1.90 – 6.57), use of repellent (OR = 3.7, 95% CI 1.58 – 8.58), and wearing long sleeves after sunset (OR = 2.5, 95% CI 0.24 – 0.84) were associated with decreased odds of Leishmaniasis infection. Leishmaniasis was discovered to be exacerbated in the study region by a lack of education, living below the poverty line, living in a temporary house, the presence of termite hills, and soil cracks near the residential area. People should eliminate dormant termite mounds near their homes, and the government should collaborate with development partners to improve people's livelihoods.